Shaking Table Deck Inclination Variation in SHP Reprocessing: X-Ray Fluorescence-Based Analysis of Sn Concentrate Grade - Khairunisa Putri Amalia; Tri Gamela Saldy; Rangga Agung Pribadi Heriawan; Heri Prabowo (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2026)
Processing residue from tin beneficiation still contains unrecovered cassiterite that can be upgraded through gravity concentration. This study describes the variation in tin (Sn) concentrate grade obtained from Sisa Hasil Pengolahan (SHP) at PT Timah Tbk under different shaking table deck inclination settings and actual plant operating conditions. Experiments were conducted at a constant water flow rate of 0.43 L/s using three deck inclinations: 1.5°, 2.0°, and 2.5°. Each condition was tested in three repetitions. Feed and concentrate samples were dried, homogenized, ground, and analyzed using X-ray fluorescence (XRF). The mean concentrate grade increased from 4.77% Sn at 1.5° to 11.58% Sn at 2.0° and 13.02% Sn at 2.5°. These results indicate that higher deck inclination within the tested range corresponded to improved concentrate grade. However, the findings remain descriptive because recovery, mass balance, and inferential statistical analysis were not included.